2020
DOI: 10.1038/s41598-020-61750-4
|View full text |Cite
|
Sign up to set email alerts
|

The risk of atrial fibrillation in patients with non-alcoholic fatty liver disease and a high hepatic fibrosis index

Abstract: Previous epidemiological studies focusing on the association between liver disease and atrial fibrillation (AF) show interesting but inconsistent findings. Patients with liver disease have a higher AF risk; however, it is unknown whether the liver fibrosis index can predict AF risk. The medical records of a healthy population undergoing routine health examinations at Healthcare System Gangnam Center, Seoul National University Hospital, were reviewed retrospectively. After excluding subjects with a history of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…FIB-4 is also useful to identify patients with liver diseases who are likely to have a liver-related adverse clinical outcome [17,18]. Importantly, FIB-4 has been shown to predict nonliver-related clinical outcomes like cardiovascular mortality or risk of atrial fibrillation in patients with MAFLD [10,19]. Likewise, FIB-4 has been shown to predict mortality in the general population [20] and clinical outcomes in nonliver-related clinical settings [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIB-4 is also useful to identify patients with liver diseases who are likely to have a liver-related adverse clinical outcome [17,18]. Importantly, FIB-4 has been shown to predict nonliver-related clinical outcomes like cardiovascular mortality or risk of atrial fibrillation in patients with MAFLD [10,19]. Likewise, FIB-4 has been shown to predict mortality in the general population [20] and clinical outcomes in nonliver-related clinical settings [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with advanced fibrosis (stages 3 and 4) present a higher risk of mortality compared with the reference population [7]. However, there is no information related to the prevalence and influence of liver fibrosis in COVID- 19.…”
mentioning
confidence: 99%
“…In addition, several studies also shown that NAFLD is associated with an increased risk of incident AF, especially among subjects with established T2DM. Park et al [118] observed that individuals with NAFLD and advanced fibrosis had a greater risk of prevalent AF even after adjusting for multiple CVD risk factors. The presence and severity of NAFLD is associated with a higher risk for corrected QT (QTc) interval prolongation resulting in an increased risk of both ventricular tachyarrhythmias and sudden cardiac death [90].…”
Section: Nafld and CV Risk: A Phatological Linkmentioning
confidence: 99%
“…Moreover, procoagulant imbalance may occur in patients with NAFLD/NASH [23]. Previous studies have demonstrated that NAFLD/NASH is independently associated with an increased risk of atrial fibrillation (AF) in adults and elderlies, especially those with type 2 diabetes mellitus (T2DM) [24,25]. Evidence also suggest a higher rate of unprovoked venous thromboembolism (VTE) in patients with NAFLD/NASH [26][27][28].…”
Section: Introductionmentioning
confidence: 99%